2011
DOI: 10.1194/jlr.m011791
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotide reduction of apoB-ameliorated atherosclerosis in LDL receptor-deficient mice

Abstract: ) mice. ISIS 147764 was administered weekly at 25-100 mg/kg for 10-12 weeks and produced dose-dependent reductions of hepatic apoB mRNA and plasma LDL by 60-90%. No effects on these parameters were seen in mice receiving control ASOs. ApoB ASO treatment also produced dose-dependent reductions of aortic en face and sinus atherosclerosis from 50-90%, with high-dose treatment displaying less disease than the saline-treated, chow-fed LDLr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…The level of hepatic steatosis observed for ApoB siRNA treatment is consistent with our previous results ( 20 ). It is worth noting, however, that liver steatosis was not reported when antisense oligonucleotides (ASO) were used to knock down ApoB ( 26 ). Following ApoB ASO treatment, modest but not signifi cant increases in hepatic triglycerides were observed at week 6 that resolved by week 20 following biweekly administration ( 27 ).…”
Section: Dgat2 Silencing Attenuates Liver Steatosis Induced By Mtp Sisupporting
confidence: 79%
“…The level of hepatic steatosis observed for ApoB siRNA treatment is consistent with our previous results ( 20 ). It is worth noting, however, that liver steatosis was not reported when antisense oligonucleotides (ASO) were used to knock down ApoB ( 26 ). Following ApoB ASO treatment, modest but not signifi cant increases in hepatic triglycerides were observed at week 6 that resolved by week 20 following biweekly administration ( 27 ).…”
Section: Dgat2 Silencing Attenuates Liver Steatosis Induced By Mtp Sisupporting
confidence: 79%
“…Second-generation ASOs targeting murine apoB (ISIS 147764), whose pharmacology has been described in detail in two previous studies (11,12), or MTP (ISIS 144477), which in primary mouse hepatocytes reduced MTP mRNA NY), where MTP activity was quantitated as described previously (16).…”
Section: Resultsmentioning
confidence: 99%
“…In earlier publications from our laboratory (11,12), we suggested that antisense suppression of apoB does not result in hepatic steatosis due to secondary compensatory changes in the expression of multiple enzymes involved in lipogenic and ␤ -oxidative pathways in the liver. Data presented here confi rm and extend those observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations